A Novel Inhalable Form of Rifapentine. Issue 5 (1st March 2014) - Chan, John G. Y.; Duke, Colin C.; Ong, Hui Xin; Chan, Joseph C. Y.; Tyne, Anneliese S.; Chan, Hak‐Kim; Britton, Warwick J.; Young, Paul M.; Traini, Daniela
<x xml:space="preserve">Abstract</x> Recent murine studies found that rifapentine, dosed daily, at least halved tuberculosis treatment times compared with standard rifampicin and isoniazid‐containing regimens. However, in humans, an inhalable form of rifapentine may be necessary to considerably shorten treatment duration because of the physiological barriers associated with oral therapy. The current study compares two inhalable rifapentine dry powders—a novel pure crystalline form and an amorphous form—by a series of in vitro tests. The crystalline and amorphous powders had a mass median aerodynamic size of 1.68 ± 0.03 and 1.92 ± 0.01 μm, respectively, associated with a fine particle fraction of 83.2 ± 1.2% and 68.8 ± 2.1%, respectively. A quinone degradation product was identified in the amorphous powder stored for 1 month, whereas the crystalline form remained chemically stable after storage at both 0% and 60% relative humidity, 25°C, for at least 3 months. Solubilized rifapentine was well tolerated by pulmonary tissue and macrophage cells up to approximately 50 μM. The accumulation of rifapentine within alveolar macrophage cells was significantly higher than for rifampicin, indicating enhanced delivery to infected macrophages. The novel inhalable crystalline form of rifapentine is suitable for targeted treatment of tuberculosis infection and may radically shorten treatment duration. © 2014 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 103:1411–1421, 2014